Using ZINC08918027 inhibitor to determine Aurora kinase-chromosomal passenger complex isoforms in mouse oocytes - Kratka, Caroline; Drutovic, David; Blengini, Cecilia S; Schindler, Karen (BMC research notes, 2022)
OBJECTIVE: Miscarriages affect 10% of women aged 25-29, and 53% of women over 45. The primary cause of miscarriage is aneuploidy that originated in eggs. The Aurora kinase family has three members that regulate chromosome segregation. Therefore, distinguishing the roles of these isoforms is important to understand aneuploidy etiology. In meiosis, Aurora kinase A (AURKA) localizes to spindle poles, where it binds TPX2. Aurora kinase C (AURKC) localizes on chromosomes, where it replaces AURKB as the primary AURK in the chromosomal passenger complex (CPC) via INCENP binding. Although AURKA compensates for CPC function in oocytes lacking AURKB/C, it is unknown whether AURKA binds INCENP in wild type mouse oocytes. ZINC08918027 (ZC) is an inhibitor that prevents the interaction between AURKB and INCENP in mitotic cells. We hypothesized that ZC would block CPC function of any AURK isoform. RESULTS: ZC treatment caused defects in meiotic progression and spindle building. By Western blotting and immunofluorescence, we observed that activated AURKA and AURKC levels in ZC-treated oocytes decreased compared to controls. These results suggest there is a population of AURKA-CPC in mouse oocytes. These data together suggest that INCENP-dependent AURKA and AURKC activities are needed for spindle bipolarity and meiotic progression.
Keywords: Animals; Aurora Kinase B; aparát dělícího vřeténka; Female; Meiosis; segregace chromozomů; Aurora kinase; Oocyte; ženské pohlaví; meióza; Oocytes; Aurora kinasa B; Mice; oocyty; Chromosomal passenger complex; myši; Protein Isoforms; Spindle Apparatus; protein - isoformy; zvířata; Chromosome Segregation